2022
DOI: 10.3389/fnut.2022.886291
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Outcomes in Childhood Obesity-Related Inflammation and Oxidative Status

Abstract: Childhood obesity is identified as one of the major public health issues to increase the risk for cardiometabolic diseases and related complications in adulthood. The literature has supported inflammation and oxidative stress as the primary underlying mechanisms involved in the pathogenesis of obesity-related diseases. Epidemiological evidence consistently shows the benefits of physical activity in the improvement of obesity-mediated inflammation and oxidative stress status. In this narrative mini-review, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The trend directly proportional to the GIH test score did not surprise us. Physical activity-induced reduction in adiposity has shown benefits in improving obesity-mediated inflammation and oxidative stress status [ 58 ]. In this regard, there are recent and very interesting contributions that demonstrate the benefit of exercise on the intestinal microbiota and its effect on intestinal metabolism [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trend directly proportional to the GIH test score did not surprise us. Physical activity-induced reduction in adiposity has shown benefits in improving obesity-mediated inflammation and oxidative stress status [ 58 ]. In this regard, there are recent and very interesting contributions that demonstrate the benefit of exercise on the intestinal microbiota and its effect on intestinal metabolism [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…PA can reduce the infiltration and activation of inflammatory cells in adipose tissue, lower the levels of circulating inflammatory factors, enhance the activity of antioxidant enzymes, and decrease the formation of oxidative damage products. This effectively improves insulin sensitivity and lipid levels, offering multiple pathways to regulate inflammation and oxidative stress responses associated with childhood obesity [ 43 ]. Furthermore, studies have observed that MVPA is associated with reductions in obesity and its related complications through multiple pathways, including associations with increased energy expenditure, improved metabolic health, regulated adipocyte factors, reduced chronic inflammation, enhanced cardiopulmonary function, and positive psychological and behavioral changes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%